Manhaj Tafsir dalam Memahami ayat-ayat Kisah dalam Al Quran - Syarifah, Umaiyatus (ULUL ALBAB Jurnal Studi Islam, 2010)
The narrative verses in the Holy Qur’an mainly function to lead the morality (akhlaq) of the society. Islam has guiding principles for interpreting such verses so that Moslems can gain objective comprehension upon them. One of the foremost principles is to view the narratives as mysterious events and only Allah SWT knows the sequential facts-say, the real chronologies– of the stories. Besides, Moslems should not rely the validity of the narratives on ahl al-kitab’s explanation. It is, finally, imperative that any stories be confirmed and rechecked across reliable sources, such as al-Qur’an, hadits, and ulama’s trustworthy interpretation (tafsir). As the interpretation of narrative verses spread very fast orally or in written, it might be unexpectedly interfered by some Israiliyat stories. This paper provides three insights to respond the subsistence of Israiliyats: first, the validity of the Israiliyats should always be questioned except when al Quran and Hadits have provided evident points of justification; second, the Israiliyats whose content is appropriate with the teachings of al Quran and hadits can enrich our religious perspectives; third, the Israiliyats whose content contradicts Islamic values (syari’ah) should be disregarded and thrown away; and fourth, it is prohibited to tell false stories.